THE TRANSMISSION MODEL OF COMMUNICATION: TOWARD A MULTIDISCIPLINARY EXPLICATION. - SAPIENZA, ZACHARY S.; VEENSTRA, AARON S.; KIRTIKLIS, KESTAS; GIANNINO, STEVE S. (ETC: A Review of General Semantics, 2016)
The article focuses on transmission model's role in defining mass communication's historicity which characterizes the action or process of communication. It mentions predominant view of communication as the activation of a linear channel and simplified model of the communication process deriving from information theory. It also mentions using cognitive linguistic framework and several fields including general semantics and linguistics.